ANALYSIS OF USE OF PHYPHOX APPLICATIONS FOR PHYSICS PRACTICUMS USING SMARTPHONES ON COLLISION MATERIAL - Puspita Sari, Mega Indah; Kuswanto, Heru; Khafid, Mohammad Abdul (Universitas Tanjungpura, 2022)
Smartphones are a physical learning medium that can support students to experiment with measurement devices. One of the smartphone apps that can be used is phyphox. The study aims to find out collision analysis lends several types of fall fields that include soil, ceramic floor areas and board fields so that it will generate data on the height, time, and energy generated when objects hit the surface. The method used is an experiment with a collision testing comparison approach with different drop fields using phyphox and stopwatch applications. The results of three experiments in the energy board field that apples produce are larger than ceramic and soil floor fields. While the results of experiments using stopwatches showed that the energy produced has a slightly greater value than using phyphox. Phyphox application can be used for practicum independently.